CFD Analyses: The Effect of Pressure Suction and Airflow Velocity on Coronavirus Dispersal - Bushra Obeidat (18288907) (2021)
Hospital emergency departments (EDs) are hubs for highly transmissible infectious diseases, posing the highest risk of viral infection transmission. With the current COVID-19 outbreak, it has become clear that the ED design needs to be altered in order to be successful in containing the pandemic. The purpose of this study is to use a computational fluid dynamics (CFD) simulation to evaluate the ventilation system design for an emergency department at a university hospital. The kinetic energy and velocity patterns of turbulence were analyzed to determine which areas of the ED were most susceptible to viral transmission. Additionally, the impact of pressure suction on COVID-19 dispersion has been investigated. Three critical areas of the ED, overnight patient beds, surgical rooms, and resuscitation rooms, all had much higher air velocity, dispersion, and mixing levels than the rest of the department’s spaces, according to the simulation findings. Air transmission from these sites to adjacent regions is a possibility in the scenario studied, increasing the likelihood of the virus spreading from these locations and infecting people in the surrounding areas. The results of these simulations may be utilized to provide recommendations to the hospital administration about the placement of inlets and outlets, the separation of areas, and the interior design of the spaces and corridors. Other Information Published in: Applied Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/app11167450